Tumor necrosis factor-α converting enzyme (TACE) increases RANKL expression in osteoblasts and serves as a potential biomarker of periodontitis - Lee, Ji-Hyun; Choi, Young-Jin; Heo, Sun-Hee; Lee, Jae-Mok; Cho, Je-Yoel (BMB reports, 2011)
Periodontitis is a very prevalent disease. Therefore, biomarkers for the early and standard diagnoses of periodontitis are urgently needed. TACE is a membrane-bound metalloprotease. Although a recent study suggested that TACE levels in GCF are elevated during periodontal disease, the levels of TACE in GCF at different stages of chronic periodontitis have not been determined. Here, we analyzed the protein levels of TACE in GCF from periodontal disease subjects and confirmed that the protein levels of TACE were higher in the moderate periodontitis groups. TACE is known to be a NF-κB ligand that stimulates RANKL secretion in osteoblasts. To understand the effects of TACE on RANKL and OPG in osteoblasts, we treated MG63 cells with TACE. We observed an increase in RANKL protein expression but a decrease in OPG protein expression. Our data suggest that TACE can induce RANKL expression and promote osteoclastogenesis, thus worsening the outcome of periodontitis.